Global Impacts of the Doha Scenarios on Poverty - Anderson, Kym (World Bank, Washington, DC, 2012)
The authors illustrate some of the potential consequences of the World Trade Organization's Doha Round of multilateral trade negotiations on incomes and poverty globally. Using the global LINKAGE model to generate changes in domestic and international prices that have a direct impact on factor incomes and consumer prices, they estimate the change in real income at the poverty line that would accompany various reform scenarios. When accompanied by additional information about the elasticity of poverty with respect to income, this provides an estimate of the change in poverty by country. Under most liberalization scenarios considered, unskilled wages rise more than average incomes, but the estimated impact on global poverty is modest, especially if developing countries are unwilling to undertake much reform.